The Influence of Oral Versus Silent Reading on Reading Comprehension in Students With Reading Disabilities. (May 2019) - Robinson, Melissa F.; Meisinger, Elizabeth B.; Joyner, Rachel E.
This study examined the effects of reading modality (oral vs. silent) on comprehension in elementary school students with a specific learning disability in reading ( N = 77). A 2 (development-level) × 2 (reading modality) × 2 (time) mixed factorial analysis of variance (ANOVA) was conducted to determine the influence of these variables on comprehension. Significant main effects were found for reading modality and time on comprehension, but the main effect for developmental level was not significant. Students understood more of what was read orally than silently and showed improved comprehension across the year. The development-level by modality interaction was significant. Early elementary students benefited from oral reading in terms of comprehension, whereas equivalent comprehension was observed for late elementary students across modalities. No other two- or three-way interactions were significant. Results from this study suggest that reading modality is an important variable to consider for researchers and educators who are interested in the construct of reading comprehension.